Antipyrexial effects of paracetamol in postcardiac surgery children. Issue 4 (11th March 2011) - Pagano, D; Wheeler, S; Mulla, H
Abstract : Objective: To determine the pharmacodynamic effects of paracetamol on pyrexia after cardiac surgery in children. To investigate if there was a dose-effect relationship. To investigate if formulation or route of administration had an effect on the antipyrexial effects. Methods: Data was collected both prospectively (over a 3 month period between June and August 2010) and retrospectively over a 12 month period between June 2009 and June 2010. Data was collected for patients on both PICU and the paediatric cardiac ward. Data was obtained from the patients medical notes, nursing notes and prescription chart. Since the reason for prescribing paracetamol (pain or pyrexia) is often not stated in the notes or prescription chart, the inclusion criteria were simplified to include all patients who had an elevated temperature, receiving paracetamol who had a core temperature recorded prior to and after paracetamol administration. Temperature was recorded hourly following paracetamol administration. All data was entered onto an Excel spreadsheet for analysis. Mean, SD and the range of uncorrected and baseline corrected temperatures post dosing were determined. Results: In total, data from 52 patients were collected (8 prospective, 44 retrospective). However, the final analysis was limited to 35 patients in whom temperature ≥ 38°C was recorded and who did not receive concomitant NSAIDs. Only one patient received intravenous paracetamol, and in the remaining subjects it was not possible to distinguish whether the oral or rectal route was used from the prescription chart. The mean age was 3 years 2 months (range 2 months–16 years 9 months), mean weight was 14.1 kg (range 3.9–71 kg), mean dose of paracetamol was 15.8 mg/kg (range 12.7–20.3 mg/kg). The ratio male/female was 1.69. The onset of antipyrexial effect of paracetamol was 1 h after PO/PR administration. The mean time to maximum antipyresis was 4.3 (range 1–6) h. The overall mean maximum decline in temperature was 1.5 (range 0.1–4.4) ° C. The relationship between dose and maximum temperature decline was analysed by categorising dose into Group 1 ≤ 16 mg/kg and Group 2 ≥ 16 mg/kg. The results revealed that the higher dose group achieved a greater temperature reduction; 1.2 versus 1.9°C (p=0.03). In 13 patients (37%), hypothermia (temperature < 36.5°C) was observed after administration of paracetamol. Although this could be interpreted as an adverse effect, the effect could not be attributed directly to paracetamol, and other factors such as environmental temperature may have influenced the findings. Conclusion: The pharmacodynamic effects of paracetamol were assessed using easily accessible clinical records. Enterally administered paracetamol is shown to reduce temperature effectively; however the time to maximum antipyrexial effect is delayed and may reflect delayed gastric empyting. A greater temperature decline (and perhaps more rapid) maybe achieved with higher doses. A prospective study is required to investigate whether formulation affects the pharmacodynamic response.